2020
DOI: 10.1007/s43452-020-00051-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate shear response of ultra-high-performance steel fibre-reinforced concrete elements

Abstract: This paper examines the experimental performance of ultra-high-performance steel fibre-reinforced concrete (UHPSFRC) beams subjected to loads at relatively low shear span-to-depth ratios. The results and observations from six tests provide a detailed insight into the ultimate response including shear strength and failure mode of structural elements incorporating various fibre contents. The test results showed that a higher fibre content results in an increase in ultimate capacity and some enhancement in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…From the analysis of the fracture surface, it was observed that the fibers are evenly distributed and orthogonal to the fracture. It is possible to conclude that the steel fibers contributed to the flexural strength of the specimens because the behavior of SFRM is similar to that observed on similar materials with the same amount of fiber volume [19]. In addition, the fracture plane spread to the top of the specimen offering residual flexural strength.…”
Section: Sfrm Residual Flexural Tensile Testsupporting
confidence: 51%
See 2 more Smart Citations
“…From the analysis of the fracture surface, it was observed that the fibers are evenly distributed and orthogonal to the fracture. It is possible to conclude that the steel fibers contributed to the flexural strength of the specimens because the behavior of SFRM is similar to that observed on similar materials with the same amount of fiber volume [19]. In addition, the fracture plane spread to the top of the specimen offering residual flexural strength.…”
Section: Sfrm Residual Flexural Tensile Testsupporting
confidence: 51%
“…5.) with the proportions reported in Table 4 [19]. The steel hooked-end fibers have a length Ls=30 mm, nominal thickness ts=0.55 mm and the mechanical properties reported in Table 5.…”
Section: Sfrm Experimental Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexural strength of a fibre-reinforced mortar is highly dependent on the embedment length and the aspect ratio of the fibre [62]. This would also be the case for an RPVC fibre/granule -mortar matrix.…”
Section: Constitutive Modellingmentioning
confidence: 97%
“…Few studies have reported on the seismic behaviour of reinforced concrete elements with SFRC. Tibea et al [13] examined the experimental performance of ultra-high-performance steel fibre reinforced concrete (UHPSFRC) beams. The test results showed that higher fibre content resulted in an increase in the ultimate capacity and some enhancement in terms of the ductility.…”
Section: Introductionmentioning
confidence: 99%